Pembentukan Karakter Peserta Didik Melalui Pembelajaran Matematika - Suparni, Mrs. (UIN Sunan Kalijaga Yogyakarta, 2012)
Character building not only as an issue of education development, but also as a process of citizen moral building. Character building as an education focus in all of education level from elementary schoolÂ into university spend a high attention. Mathematics education canât release from mathematics. So, If we want to build the student character, we must be use the philosophies values of mathematics education by expression the characteristic of mathematics as the object is abstract, the symbol is no meaning, agreement reached and deductive axiomatic thinking, and non contradiction. There are many character value in the mathematics instruction that related with the characteristic of mathematics that can be integrated with Al Qurâan that we hope can support national education purposes, as agreement reached, consistent, deduction and whole. The student character canÂ be build by mathematics instruction as religious, truth, tolerance, discipline, creative, democratic,Â sense to know, nationality, and communicative.